Iron Oxide Nanoparticles: Preparation, Characterization, and Assessment of Antimicrobial and Anticancer Activity. (11th March 2022) - Alangari, Abdulaziz; Alqahtani, Mohammed S.; Mateen, Ayesha; Kalam, Mohd Abul; Alshememry, Abdullah; Ali, Raisuddin; Kazi, Mohsin; AlGhamdi, Khalid M.; Syed, Rabbani
Abstract : Nanotechnology and nanoparticles (NPs) have increasingly been studied as an alternative for antibiotics because of the feasibility to be used in implantable devices both for bacterial detection and infection prevention. The low rate of resistance development against NPs because of its multiple mode of action has contributed to its increased acceptance in clinical setting. Further development of NPs and their anticancer activity against many human cancer cell lines including breast and ovarian have been documented. Fe2 O3 -NPs could be used for antibacterial and anticancer activity assessment. Iron oxide, apart from being available extensively and cheap, also plays a role in multiple biological processes, making it an interesting metal for NPs. The aim of the present study revolves around generation and characterization of iron oxide Fe2 O3 -NPs, followed by assessment of its antimicrobial and anticancer activities. Synthesis of Fe2 O3 -NPs was performed by hydrothermal approach, and its characterization was done by UV-visible, X-ray diffraction (XRD), Fourier-transform infrared spectroscopy (FTIR) analyses, and transmission electron microscopy (TEM). Antimicrobial activity was checked by agar diffusion assay against Bacillus subtilis, Pseudomonas aeruginosa, Staphylococcus aureus, Escherichia coli, and Candida albicans . Anticancer activity of the NPs was assessed using the human cancer cell lines including cervical carcinoma cell line (HeLa) and MCF7. The developed Fe2 O3 -NPs exhibited a characteristic absorption curve in the 500-600 nm wavelength range by UV-visible analysis, the XRD peaks were found to index the rhombohedral shape, and the FTIR analysis ascertained the bonds and functional groups at wavenumber from 400 to 4000 cm -1 . Antimicrobial assay detected significant effect against Staphylococcus aureus and Bacillus subtilis with zones of inhibition: 21 and 22 mm, respectively. Likewise, Fe2 O3 -NPs show good activity towards tested fungal strain Candida albicans with zone of inhibition of 24 mm. The 2, 5-diphenyl-2H-tetrazolium bromide (MTT) assay identified significant anticancer activity of the NPs against both cell lines. Our study documents the successful generation and characterization of Fe2 O3 -NPs having excellent antimicrobial and anticancer activities.